Association between skipping breakfast and risk of cardiovascular disease and all cause mortality: A meta-analysis. Issue 10 (October 2020) - Chen, Hanze; Zhang, Beidi; Ge, Yusong; Shi, Han; Song, Siqi; Xue, Weishuang; Li, Jinwei; Fu, Kailei; chen, Xinxin; Teng, Weiyu; Tian, Li
Summary: Background & aims: Previous studies on the association between skipping breakfast and risk of cardiovascular disease and all cause mortality have drawn controversial conclusions. Therefore, we carried out a meta-analysis to illuminate this association. Methods: Studies about the association between skipping breakfast and risk of cardiovascular disease and all cause mortality were identified by searching Pubmed, Embase, Cochrane, and Web of Science databases until June 2019. Then we screened articles for eligibility, extracted data, and pooled the results using a random-effects model. Results: Seven cohort studies concerning a total of 221, 732 participants were included in this meta-analysis. Skipping breakfast was associated with elevated risk of cardiovascular disease (relative risk 1.22 95% confidence interval 1.10–1.35) and all cause mortality (relative risk 1.25 95% confidence interval 1.11–1.40) compared with eating breakfast regularly. Conclusion: Skipping breakfast increases the risk of cardiovascular disease and all cause mortality. Eating breakfast regularly may promote cardiovascular health and decrease all cause mortality.